(untitled) (Bodhi Path, 2025)
Dr. B.R. Ambedkar’s popular name was "Babasaheb Ambedkar." Babasaheb was the architect of the Indian Constitution and is also regarded as a prominent global leader and jurist. His efforts toward the upliftment of society and his contributions were of immense significance. Babasaheb made outstanding efforts against social evils such as untouchability, caste hierarchy, and the varna system through relentless struggle. Throughout his life, he fought for the rights of Dalits and other socially disadvantaged groups. His major contribution was his vital role in drafting the Indian Constitution after independence. He served as the Chairman of the Drafting Committee of the Constitution. His contributions are remembered as those of a key architect in the creation and establishment of various institutions in independent India. Dr. Ambedkar was appointed as the first Law Minister of independent India in Jawaharlal Nehru’s cabinet. On October 14, 1956, he embraced Buddhism and initiated a significant religious transformation. Posthumously, the Government of India honored him with the Bharat Ratna award in 1990. This research paper has been compiled based on various sources.